Life cycle water footprint assessment of concrete production in Northwest China - Chao Ding (IWA Publishing, 2021)
Concrete requires a large amount of water throughout the product life cycle. This study constructs a comprehensive evaluation model of the life cycle water footprint (LCWF) of concrete production. It calculates the LCWF of concrete in Northwest China. The main conclusions are: (1) The vast water consumption of the concrete industry is closely related to VWF, which is the focus of LCWF assessment. The first three significant factors are WF of Coarse aggregate, Meals, and Cement. (2) the overproduction of cement is 15,731 × 104t, which results in the excessive consumption of water resources of 24,035 × 104m3. Excessive water consumption in the domestic cement trade is equivalent to an outflow of water resources. (3) The water stress index (WSI) of Northwest China is 0.67 (in Heavy pressure). The WSI of Qinghai (0.05) and Shaanxi (0.5) are in Mild pressure and Moderate pressure, respectively, while the WSI of Gansu is 0.67 (in Heavy pressure). It is worth noting that the WSI of Ningxia (9.01) and Xinjiang (1.28) are under Extreme pressure. The sustainable development of water resources in Northwest China is under heavy pressure, exacerbated by the growth of the concrete and cement industries. HIGHLIGHTS This study constructs a comprehensive evaluation model of the LCWF of concrete production in Northwest China.; The first three sensitivity factors are WF of Coarse aggregate, Meals, and Cement.; The overproduction of cement is 157.31 million tons, which results in the excessive consumption of water resources of 240.35 million cubic meters.; The WSI of Northwest China is 0.67 (in Heavy pressure).;